Cholinomimetic Properties of a Water-Soluble Fraction from Mulberry Leaves in Rats - Changbae JIN; Yong Sup LEE; Sung-Hyun CHUNG; Ju-Seon LEE (한국응용약물학회, 2005)
The present study examined effects of a water-soluble fraction from mulberry leaves (ML water fraction) on the circulatory and autonomic nervous systems, which were compared with those of acetylcholine (ACh) used as a reference drug in order to elucidate its mechanism of action. Intravenous administration of ACh or a ML water fraction produced temporary depressor and tachycardiac responses in a dose-dependent manner in unrestrained, conscious Sprague-Dawley rats. The systemic hemodynamic effects of ACh and a ML water fraction were almost completely blocked by pretreatment with atropine, a muscarinic antagonist. The depressor responses to ACh and a ML water fraction were slightly enhanced and prolonged by pretreatment with neostigmine, an anticholinesterase, whereas the tachycardiac responses were remarkably blocked by pretreatment with pentolinium, a ganglionic blocking agent. In vitro experiments using the ileum isolated from rats showed that ACh and a ML water fraction increased ileal contractility in a dose-dependent manner. The increases in ileal contractility were also completely abolished in the presence of atropine. Finally, the specific binding of [3H]quinuclidinyl benzilate, a muscarinic antagonist, to rat cortical synaptic membranes was inhibited by a ML water fraction in a concentration- dependent manner with an IC50 value of 9.5 mg/ml. The results suggest that the effects of a ML water fraction are mediated through direct stimulation of muscarinic cholinergic receptors by unknown cholinomimetic substance(s) contained in that fraction.